Dual-Chamber pacing for postoperative residual left ventricular gradient after aortic valve replacement and concomitant septal myectomy for severe aortic stenosis and subvalvular obstruction. Issue 1 (July 2020) - Imafuku, Hikaru; Komatsu, Junya; Imai, Ryuichiro; Ohsawa, Naoto; Nakaoka, Yoko; Kubokawa, Sho-ichi; Kawai, Kazuya; Hamashige, Naohisa; Doi, Yoshinori
Abstract: Background: Aortic stenosis is occasionally associated with subvalvular obstruction and remaining obstruction may at times be found after aortic valve replacement. Case report: A 69-year-old woman with a history of several episodes of unconsciousness was admitted because of exertional chest oppression. The echocardiography revealed severe aortic stenosis (flow velocity 6.2 m/sec, maximum / mean pressure gradient 152 / 99 mmHg, valve area 0.59 cm2) as well as gradient within the left ventricular cavity from the mid ventricular level (flow velocity 4.5 m/sec, maximum gradient 82 mmHg). Despite aortic valve replacement and concomitant septal myectomy which was thought adequate in reducing subvalvular pressure gradient during surgery, postoperative echocardiography revealed significant residual mid ventricular gradient (flow velocity 4.9 m/sec, maximum gradient 95 mmHg). It was decided to implant dual-chamber pacemaker, which resulted in significant reduction of residual mid ventricular gradient (flow velocity 1.4 m/sec, maximum gradient 8 mmHg). Conclusion: Dual-chamber pacing was extremely effective in reducing residual mid ventricular gradient in a patient who underwent aortic valve replacement and concomitant septal myectomy for severe aortic stenosis and subvalvular obstruction. <Learning objective : Dual-chamber pacing was extremely effective in reducing residual mid-ventricular pressure gradient in a 69-year-old woman with antecedent aortic valve replacement and concomitant septal myectomy for severe aortic stenosis and subvalvular obstruction. Dual-chamber pacing may have the potential to become one of the non-surgical therapeutic options for those with post-surgical residual subvalvular gradient, not only for severe aortic stenosis and subvalvular obstruction but also for obstructive hypertrophic cardiomyopathy.>